A Study on Reward System on Employee Performance (With Special Reference to KPR Cars PVT LTD Volkswagen Mysore) - M.P, Bhavya.P; Somashekar, M.P (Pusat Publikasi Nusantara, 2023)
Rewards and incentives are “important aspect in today’s competitive environment. As the role of rewards has grown, a lot of changes have been taking place in the reward system, so while making a reward strategy, a type of industry and their involvement is considered.” In earlier times, the manager faces a problem of huge turnover of employees due to which an employee never has a bond with his employer. So, a manager decided to retain their highly talented employee by motivating them so that the quality of work would be maintained. Employee reward is one of the methods of motivating employees increasing employee performance, which benefit the organization. Reward involves the management of expectations in which both employer and employee except from each other. The employer wants the maximum contribution of their employer, and employees want their effort to be matched with their pay in return of their pay. Then, of reward management takes place which involves the strategy and policies related to pay